Question 3 and 4, Exercise 4.8
Solutions of Question 3 and 4 of Exercise 4.8 of Unit 04: Sequence and Series. This is unit of Model Textbook of Mathematics for Class XI published by National Book Foundation (NBF) as Federal Textbook Board, Islamabad, Pakistan.
Question 3
Using the method of difference, find the sum of the series: $1+4+13+40+121+ \ldots$ to $n$ term.
Solution. Let $$ S_{n}=1+4+13+40+121+\ldots +T_{n} $$ Also $$ S_{n}=1+4+13+40+\ldots +T_{n-1}+T_{n}. $$ Subtracting the second expression from the first expression, we have \begin{align*} S_{n}-S_{n}& =1+4+13+40+121+\ldots +T_{n} \\ & -\left(1+4+13+40+\ldots +T_{n-1}+T_{n}\right) \end{align*} \begin{align*} \implies 0=&1+(4-1)+(13-4)+(40-13)+(121-40) \\ & +\ldots+(T_{n}-T_{n-1})-T_{n}. \\ \implies 0=&1+(3+9+27+81+\ldots \text { up to } (n-1) \text { terms })-T_{n} \end{align*} Then \begin{align*} T_{n} & =1+(3+9+27+81+\ldots \text { up to }(n-1) \text { terms }) \\ & =1+\frac{3(3^{n-1}-1)}{3-1} \quad\left(\because S_{n}=\frac{a(r^n-1)}{r-1}\right) \\ & =1+\frac{3^{n}-3}{2} \\ & =\frac{2+3^{n}-3}{2} \\ \\ & =\frac{3^{n}-1}{2}. \end{align*} Thus, the kth term of the series: $$ T_{k}=\frac{3^{k}-1}{2}. $$ Now taking the sum, we get \begin{align*} S_{n} & =\sum_{k=1}^{n} T_{k}=\sum_{k=1}^{n} \frac{3^{k}-1}{2} \\ & =\frac{1}{2}\left(\sum_{k=1}^{n} 3^{k} - \sum_{k=1}^{n} 1\right) \\ & =\frac{1}{2}\left((3+3^2+3^3+\ldots +3^{n})-n\right) \\ & =\frac{1}{2}\left(\frac{3(3^n-1)}{3-1}-n\right) \\ & =\frac{1}{2}\left(\frac{3^{n+1}-3}{2}-n\right) \\ & =\frac{1}{4}(3^{n+1}-3-2n). \end{align*} Hence, the sum of the given series is \( \frac{1}{4}(3^{n+1}-3-2n) \).
Question 4
Using the method of difference, find the sum of the series: $1+2+4+7+11+16+\ldots$ to $n$ term.
Solution.
Let $$ S_{n}=1+2+4+7+\ldots +T_{n} $$ Also $$ S_{n}=1+2+4+7+\ldots +T_{n-1}+T_{n}. $$ Subtracting the second expression from the first expression, we have \begin{align*} S_{n}-S_{n}& =1+2+4+7+\ldots +T_{n} \\ & -\left(1+2+4+7+\ldots +T_{n-1}+T_{n}\right) \end{align*} \begin{align*} \implies 0=&1+(2-1)+(4-2)+(7-4)+\ldots+(T_{n}-T_{n-1})-T_{n}. \\ \implies 0=&1+(1+2+3+ \ldots \text{ up to } (n-1) \text{ terms })-T_{n}. \end{align*} Then \begin{align*} T_{n} & =1+(1+2+3+\ldots \text{ up to }(n-1) \text{ terms }) \\ & =1+\frac{n-1}{2}[2(1)+(n-1-1)(1)] \quad \left(\because S_n=\frac{n}{2}[2a + (n-1)d]\right) \\ & =1+\frac{(n-1)n}{2}. \\ & =\frac{2+n^2-n}{2}. \\ & =\frac{1}{2}(n^2-n+2). \end{align*} Thus, the \(k\)-th term of the series is: $$ T_{k}=\frac{1}{2}(k^2-k+2). $$ Now, taking the sum, we get \begin{align*} S_{n} & =\sum_{k=1}^{n} T_{k}=\sum_{k=1}^{n} \left(\frac{1}{2}(k^2-k+2)\right) \\ & = \frac{1}{2} \sum_{k=1}^{n} k^2 - \frac{1}{2} \sum_{k=1}^{n} k + \sum_{k=1}^{n} 1\\ & =\frac{1}{2} \left(\frac{n(n+1)(2n+1)}{6}\right) - \frac{1}{2} \left(\frac{n(n+1)}{2}\right)+n \\ & =\frac{n}{12}\left((n+1)(2n+1)-3(n+1)+12 \right) \\ & =\frac{n}{12}\left(2n^2+2n+n+1-3n-3+12 \right) \\ & =\frac{n}{12}\left(2n^2+10 \right) \\ & =\frac{n}{6}\left(n^2+5 \right) \\ \end{align*} Thus $$ S_{n} = \frac{n}{6}\left(n^2+5 \right). $$
Go to